A randomized, double-blind, parallel pharmacokinetic study comparing the trastuzumab biosimilar candidate, AryoTrust®, and reference trastuzumab in healthy subjects - Farmahini Farahani, Mohammad; Maghzi, Parnian; Jafari Aryan, Nazanin; Payandemehr, Borna; Soni, Mayur; Azhdarzadeh, Morteza (Expert opinion on investigational drugs, 2020)
AryoTrust® (AryoGen Pharmed Co., Iran) is a biosimilar candidate for the EU-sourced reference trastuzumab, Herceptin®. This study was designed to evaluate the bioequivalence between AryoTrust® and Herceptin®. In this double-blind, parallel study, 60 healthy male subjects were randomized 1:1 to receive a single dose of AryoTrust® or Herceptin® (6 mg/kg) as intravenous infusion. The primary endpoint of the study was the area under the concentration versus time to infinity (AUC ), and the main secondary endpoints were maximum measured concentration (C ), area under the concentration versus time from zero to the last quantifiable concentration time (AUC ), immunogenicity, and safety. Sixty subjects were enrolled in the study and baseline demographics were similar between the two groups. The two groups demonstrated similar pharmacokinetic parameters and the 90% confidence interval (CI) for primary and secondary endpoints were within the bioequivalence acceptance range (80.00%-125.00%). No serious adverse event or immunogenicity was reported, and all of the adverse events reported were mild and similar between the two treatment groups. AryoTrust® was well tolerated, had a similar safety profile to reference trastuzumab, and its pharmacokinetic bioequivalence was confirmed. The trial is registered at Indian Trials Registry (CTRI/2019/03/018218).